Three new species of Eurypon Gray, 1867 from Northeastern Brazil (Poecilosclerida; Demospongiae; Porifera) - Santos, George Garcia; França, Fernando; Pinheiro, Ulisses (Zootaxa, 2014)
Three new species of Eurypon from Northeastern Brazil are described: Eurypon clavilectuarium sp. nov.; Eurypon suassunai sp. nov. and Eurypon distyli sp. nov. Samples were collected from the continental shelf of Rio Grande do Norte, Bahia and Paraíba States. While the majority of Atlantic Eurypon species have been described from deep water, two of three new species described in this study were collected from shallow depths. The three new species from Brazil were compared with all other eighteen Eurypon species described from the Atlantic.